International Society of Photogrammetry and Remote Sensing - (:unkn) unknown (My University, 2026)
Photogrammetry is the science and technology of extracting reliable three-dimensional geometric and thematic information, often over time, of objects and scenes from image and range data. Remote sensing is the science and technology of capturing, processing and analysing imagery, in conjunction with other physical data of the Earth and the planets, from sensors in space, in the air and on the ground. Spatial Information Science is concerned with the modelling, storage, processing, retrieval, application and communication of information with a spatial reference. The International Society for Photogrammetry and Remote Sensing is a non-governmental organization devoted to the development of international cooperation for the advancement of photogrammetry and remote sensing and their applications. The Society operates without any discrimination on grounds of race, religion, nationality, or political philosophy.